On the M-Projective Curvature Tensor of N(κ)-Contact Metric Manifolds. (26th March 2013) - Singh, R. N.; Pandey, Shravan K.
Abstract : The object of the present paper is to study some curvature conditions on N ( κ ) -contact metric manifolds.